2023
DOI: 10.1038/s41398-023-02526-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in neural mechanisms underlying post-traumatic stress disorder in World Trade Center responders

Abstract: World Trade Center (WTC) responders exposed to traumatic and environmental stressors during rescue and recovery efforts have a high prevalence of chronic WTC-related post-traumatic stress disorder (WTC-PTSD). We investigated neural mechanisms underlying WTC-PTSD by applying eigenvector centrality (EC) metrics and data-driven methods on resting state functional magnetic resonance (fMRI). We identified how EC differences relate to WTC-exposure and behavioral symptoms. We found that connectivity differentiated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Pioneering studies using neuroimaging approaches have identified functional changes in multiple brain areas, including the hippocampus, amygdala, anterior cingulate cortex (ACC), insular cortex, and ventromedial prefrontal cortex, in patients with PTSD. [ 4 , 5 ] However, the brain areas and circuits involved in abnormal fear memory extinction are poorly understood. Clinical studies have revealed no differences in the acquisition phase of memory in patients with PTSD, [ 6 , 7 ] suggesting the presence of specific areas beyond the well‐known memory control centers in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies using neuroimaging approaches have identified functional changes in multiple brain areas, including the hippocampus, amygdala, anterior cingulate cortex (ACC), insular cortex, and ventromedial prefrontal cortex, in patients with PTSD. [ 4 , 5 ] However, the brain areas and circuits involved in abnormal fear memory extinction are poorly understood. Clinical studies have revealed no differences in the acquisition phase of memory in patients with PTSD, [ 6 , 7 ] suggesting the presence of specific areas beyond the well‐known memory control centers in the brain.…”
Section: Introductionmentioning
confidence: 99%